Living well in the Neuropolis. Issue 1 (March 2016) - Fitzgerald, Des; Rose, Nikolas; Singh, Ilina
Abstract: This paper is about the relationship between cities and brains: it charts the back‐and‐forth between the hectic, stressful lives of urban citizens, and a psychological and neurobiological literature that claims to make such stress both visible and knowable. But beyond such genealogical labour, the paper also asks: what can a sociology concerned with the effects of 'biosocial' agencies take from a scientific literature on the urban brain? What might sociology even contribute to that literature, in its turn? To investigate these possibilities, the paper centres on the emergence and description of what it calls 'the Neuropolis ' – a term it deploys to hold together both an intellectual and scientific figure and a real, physical enclosure. The Neuropolis is an image of the city embedded in neuropsychological concepts and histories, but it also describes an embodied set of (sometimes pathological) relations and effects that take places between cities and the people who live in them. At the heart of the paper is an argument that finding a way to thread these phenomena together might open up new paths for thinking about 'good' life in the contemporary city. Pushing at this claim, the paper argues that mapping the relations, histories, spaces, and people held together by this term is a vital task for the future of urban sociology.